Pendidikan Multikultural Sebagai Upaya Menanamkan Nilai-Nilai Keberagaman Dalam Islam Pada Anak Usia Dini - Fauzi Fauzi (Departement of Mathematics Education, 2023)
In Islam, Islamic education also plays an important role in instilling diversity values as strengthening multicultural values in children from an early age. Not only that, Islam also teaches children to interact with friends who can also provide educational values that are multicultural in mind in realizing children who are obedient in religion and respect other religions.In this study, using qualitative research methods. Qualitative methods are used to obtain data that contains meaning about the social reality that is observed and then interpreted thoroughly and comprehensively. The data collection in this study is descriptive-qualitative in nature, in which the researcher does not intend to test the hypothesis. This research resulted in the conclusion that there are values of diversity that can be used as multicultural education in early childhood in Islam as explained in the Qur'an, namely: (1) Ta'aruf (Knowing Each Other), ( 2) Egalitarian (Equal Degrees), Taqwa (Degrees of Piety). Multicultural education like this will build the soul of early childhood not to distinguish people who are different from them.